Possible involvement of reusable towels in the high rate of Bacillus species-positive blood cultures in Japanese hospitals. Issue 2 (February 2016) - Saito, Norihiro; Kondo, Jun; Haruki, Shigeki; Itoga, Masamichi; Yamamoto, Ayako; Kimura, Masahiko; Inoue, Fumio; Kobayashi, Masakazu; Tsutaya, Shoji; Kojima, Keiya; Ueki, Shigeharu; Hirokawa, Makoto; et al.
Abstract: Background: A number of outbreaks caused by Bacillus species have been reported to date. Outbreaks reported in the last decade have predominantly arisen in Japanese hospitals. Aim: To elucidate factors contributing to these real or pseudo outbreaks by Bacillus species, and to evaluate the rate of Bacillus species-positive blood culture samples in Japan. Methods: A systematic review of the literature was performed. Reports including data on outbreaks caused by Bacillus species were searched for in PubMed, Google Scholar and Evidence-based Medicine BMJ from inception through 10 Aug 2014. Japanese nationwide data on bacteriological tests were collected from Japan Nosocomial Infections Surveillance. Regional bacteriological data for Akita prefecture were collected using the Akita Regional Network for Infection Monitoring/Control System. Findings: Contamination of reusable towels was suspected as a cause for the high rate of Bacillus -positive blood cultures in Japan. The rate of Bacillus species in blood cultures was much higher in Japan than in reports from other countries. Conclusions: The high contamination rate of blood culture samples by Bacillus species in Japan is a matter of concern for infection control and medical treatment. Bacteriological investigation of reusable towels should be considered in hospitals with a high frequency of Bacillus -positive blood cultures.